Compound semiconductor nanowires based organicinorganic hybrid solar cell - Wu, Dan (2017)
As the demand for clean and sustainable energy sources increases, extensive research attention has been directed to photovoltaics owing to its inexhaustibility, abundance and wide availability. Despite the great efforts devoted, reasonable efficiency and price reduction are still the main issues to enable the solar cells to be fully competitive with traditional energy sources. Organic photovoltaics have provided a low-cost solution but the low efficiency and reliability issues threaten their wide application. Semiconductor nanowire (NW) arrays have demonstrated great potential for solar energy harvesting and material reduction. However, the lack for optimization and fabrication cost limit their large scale implementation. To further reduce the cost and improve the performance of the photovoltaics, hybrid solar cells (HSCs) based on III-V NWs and organics have emerged as promising candidates to combine the advantages of inorganic and organic materials. In this work, we unravel the role of III-V semiconductor NWs in the inorganics-organics HSCs through theoretical modeling, numerical simulation, device fabrication and characterization. First of all, an effective and efficient algorithm was provided to guide the design of geometrical dimensions for NW arrays to achieve maximal solar energy harvesting regardless of the materials, single or multiple diameters, and the arrangements of NW arrays. Compared with time-consuming numerical simulations, the proposed method maintained a low tolerance of below 2.2% for all cases. Next, an opto-electrical model was built to fully evaluate the performance of the GaAs NWs based HSCs elaborating the light absorbing features and electrical characteristics. Validation with the published experimental results had proved the effectiveness of the above two theoretical work. Thirdly, HSCs based on vertically aligned GaAs NWs fully-infiltrated by poly(3-hexylthiophene-2,5-diyl) (P3HT) were fabricated and characterized. Well control over the diameters and periodicities of the GaAs NW arrays was realized by combining nanospheres lithography and dry etching. The role of the geometrical parameters of the GaAs NW arrays was investigated by characterizing the performance of HSCs. The power conversion efficiency (PCE) of the HSC reached 4.6% with the optimized GaAs NW arrays dimensions. We have also demonstrated a new prototype of low-cost GaAs NWs HSC. Freely standing GaAs NWs were for the first time directly grown on low-cost substrate of indium tin oxide (ITO) glass using Au nanoparticles as the catalysts by metal organic chemical vapor deposition (MOCVD). The size and area density controllable Au nanoparticles deposition by droplet-only method and centrifugation technique were initially developed to control over the diameters, position and the density of the as-grown NWs. Quantitatively and qualitatively study of the growth parameter’ influence was also carried out to evaluate and optimize the growth of the GaAs NWs. Freely standing GaAs NWs of various sizes and area densities with high crystal quality were obtained. Based on these results, a prototype of the GaAs NWs/P3HT HSCs was developed which provided a new pathway of low-cost HSCs.